Short Communication: Increase of Sialylated N-Glycansin Eyes with Neovascular Glaucoma Secondary to Proliferative Diabetic Retinopathy. (3rd May 2016) - Inafuku, Saori; Noda, Kousuke; Amano, Maho; Nishimura, Shin-Ichiro; Ishida, Susumu
Abstract: Purpose : To investigate the alteration of N -glycans in the vitreous fluid of patients with neovascular glaucoma (NVG) secondary to proliferative diabetic retinopathy (PDR). Methods : Vitreous samples were collected from 18 patients with PDR (including 7 with NVG and 11 without NVG), and 17 patients without diabetes. Profiles of N -glycans were analyzed by glycoblotting-based high throughput protocol, which we recently developed. Protein levels of vascular endothelial growth factor (VEGF)-A were measured by ELISA. Results : The concentration of total N -glycans and the concentration of N -glycans with sialic acids were significantly higher in NVG group compared with those in non-NVG group or control group, whereas there was no significant difference in concentrations of high-mannose N -glycans among three groups. There was a moderate correlation between the concentrations of sialylated N -glycans and VEGF-A. Conclusions : Our data demonstrate the distinct changes of N -glycan profile and the increase of sialylated N -glycans in eyes with NVG secondary to PDR.